A FUNED como uma organização pública para a inovação: uma proposta de estrutura organizacional para a área de pesquisa e desenvolvimento - Bruno Coelho Resende de Castro (2019)
Organizational structures are important elements within innovation process and influence people's action who shape and are shaped by those structures. Some organizations aiming at innovation can face a dilemma when it comes to balancing different approaches in their organizational structures: while there may be a need for social constraint through well-defined control and limits to action, this could hinder innovation, therefore raising the issue of employing a different structure which enables social action. Public Institutes of Research are framed within this approach – there are mandatory bureaucracy aspects on its structures and at the same time, their purpose is to innovate. Within that context, elements such as innovation strategy, support from the strategic apex, organizational flexibility, autonomy for people and teams, shared learning, leadership for innovation and innovative environment are aspects that must exist together with the bureaucratic structure of the State. This work aim at understanding the innovation process within a Public Institute of Research in order to propose a structure that is able to balance both social constraint and social action approaches. In order to do this, a case study has been conducted at the Brazilian public institute Fundação Ezequiel Dias (FUNED), focusing in the Research and Development Department. Interviews with researchers and managers at FUNED were conducted to understand the innovation process and how it happens, as well as to understand its issues and peculiarities. The main findings point that the innovation process is not only complex but also happens in a diverse range of ways within the department. The case was analyzed according to the literature as to propose a new organizational structure based on the institute's context and considering its particularities. The proposed changes are based in aspects as emergent strategy, teamwork with autonomy, community of practices, networking and flexibility at the organization.